The Role Of Self-Compassion In Romantic Relationship And Psychological Well-Being Among Emerging Adults In Malaysia - Teoh, Hooi Ping (2023)
The primary purpose of this study was to examine the relationship between self-compassion, romantic relationship satisfaction, psychological well-being, as well as gender and ethnic differences in relation to self-compassion, among Malaysian emerging adults. This study specifically examined the mediating effect of trust (Trust in Close Relationship Scale), love expression (Adaptive Version of Affection Communication Scale), and commitment (The Commitment Scale) in the relationship between self-compassion (Self- Compassion Scale) and romantic relationship satisfaction (Relationship Assessment Scale).